The Influence of Religious Motivation and Students Learning Outcomes in Islamic Religious Education Towards Students Tolerance Attitude - Rika Sa’diyah (TARBIYA: Journal of Education in Muslim Society, 2015)
Abstract The objective of this research is to find out the direct-indirect effects of religious motivation and PAI (Aqidah-Ibadah) learning outcomes on the attitude of tolerance. The method used in this research is path analysis. Subject of this research is selected randomly of 60 students from Muhammadiyah Senior High School Ciputat South Tangerang. The research findings are: (1) there are direct effects of religious motivation to Aqidah-Ibadah learning achievement; (2) there are direct effects of Aqidah-Ibadah learning achievement to the attitude of tolerance; (3) there are no direct effects of religious motivation to the attitude of tolerance; and (4) there are indirect effects of religious motivation to the attitude of tolerance through Aqidah-Ibadah learning achievement. These findings come up with a conclusion that students’ religious motivation affect the attitude of tolerance if they go through religious learning, It is because both the direct effects of religious motivation on religious learning achievement and the direct effects of religious learning on the attitude of retolerance are high. Therefore, all of students’ religious practices will be better if they go through religious learning and students’ religious learning will be better if they have high religious motivation. Abstrak Penelitian ini bertujuan untuk mencari pengaruh langsung dan tidak langsung motivasi beragama dan hasil belajar PAI terhadap sikap toleransi siswa. Metode yang digunakan dalam penelitian ini adalah path analisis. Sampel dalam penelitian ini dipilih secara acak yaitu 60 siswa SMA Muhammadiyah Ciputat Tangerang Selatan. Penelitian ini menemukan: (1) ada pengaruh langsung motivasi beragama terhadap hasil belajar PAI; (2) ada pengaruh langsung hasil belajar PAI terhadap sikap toleransi siswa; (3) ada pengaruh langsung motivasi beragama terhadap sikap toleransi siswa; (4) ada pengaruh tidak langsung motivasi beragama terhadap sikap toleransi siswa melalui hasil belajar PAI. Penemuan ini menyimpulkan motivasi beragama siswa berpengaruh pada sikap toleransi jika mereka belajar agama. How to Cite:  Sa’adiyah, R. (2015). The Influence of Religious Motivation and Students Learning Outcomes in Islamic Religious Education Towards Students  Tolerance Attitude. TARBIYA: Journal Of Education In Muslim Society, 2(1), 70-82. doi:10.15408/tjems.v2i1.1672. Permalink/DOI: http://dx.doi.org/10.15408/tjems.v2i1.1672